The perceived ideal qualities of secondary school mathematics leaders - Hj Ali Mashod, Mohd Khairul Azam; Pengiran Omar, Dk Nurul 'Izzati; Khanafiah, Nadiah Maimunah; Haji Alias, Nurul Hafizah; Tan, Sil Yin; Haji Mosli, Ani Afifah; Abdullah, Nor Azura; Shahrill, Masitah (Journal of Honai Math, 2022)
Effective school leadership is critical for school success. Teachers as leaders have extraordinary influences not only in their classrooms but also in the general school framework. The aspect of teacher leadership provides self-knowledge and the courage to act on that knowledge. However, there is no consensus on what defines teacher leaders and the specific qualities that characterise them. In this study, the insights of twelve conveniently sampled graduate teacher candidates in one of the teacher training institutions in Brunei Darussalam were explored. They were asked to describe the ideal leadership qualities that a secondary school mathematics teacher leader should possess. There were many variations in their responses. However, the overarching finding was that mathematics teacher leaders should have ideal qualities that make them functional within and outside of the classroom. Key attributes such as effective classroom management, content and pedagogical knowledge, effective communication and problem-solving skills, and the ability to contribute to maintaining a healthy school-community partnership were mentioned. This study concluded that in defining teacher leadership, it is essential to define the concept based on teachers’ ability to influence others to achieve set goals within and outside of the classroom.